2017
DOI: 10.1136/heartjnl-2017-311161
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibition restores orthostatic tolerance in young vasovagal syncope patients

Abstract: Objective Syncope is sudden transient loss of consciousness and postural tone with spontaneous recovery; the most common form is vasovagal syncope(VVS). We previously demonstrated impaired post-synaptic adrenergic responsiveness in young VVS patientswas reversed by blocking nitric oxide synthase(NOS). We hypothesised that nitric oxide may account for reduced orthostatic tolerance in young recurrent VVS patients. Methods We recorded haemodynamics in supine VVS and healthy volunteers (aged 15–27 years), challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…It can be inferred that reactivity to nitrates increases with the presence of TNF leading to vasodilation. The results of Stewart et al 1 are encouraging for clinical practice as we agree with the authors that there could be a role for NO modulation in the treatment of this common disease.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…It can be inferred that reactivity to nitrates increases with the presence of TNF leading to vasodilation. The results of Stewart et al 1 are encouraging for clinical practice as we agree with the authors that there could be a role for NO modulation in the treatment of this common disease.…”
supporting
confidence: 84%
“…Stewart et al 1 reported a very ingenious study that finally demonstrated the previously controversial role of nitric oxide (NO) in vasovagal syncope (VVS). They used a different approach that certainly explains that they have obtained positive findings.…”
mentioning
confidence: 99%
“…We also showed that inhibiting NO synthesis increased adrenergic vasoconstriction, increased SVR and splanchnic vasodilation, and normalized orthostatic tolerance in young patients with VVS (Stewart et al. , ). Blood flow and vascular resistance responses to orthostatic stress in our current Control‐Faint group were similar to those found previously in recurrent VVS patients, findings caused exclusively by decreased SVR.…”
Section: Discussionmentioning
confidence: 69%
“…B u t i f N O i n d u c e d vasodilation overcomes the adrenergic vasoconstrictor effect, the resulting vasodilation will contribute to a possible VVS. That this happens in young adults with recurrent VVS was elegantly demonstrated by Stewart et al (74). They concluded that in patients with recurrent VVS, there is large scale vasodilation, particularly in the splanchnic bed which is mediated by NO which is secreted by neuronal NO via nitrergic nerves, a nomenclature suggested by Toda et al (75) to describe neuronal N O s y n t h e s i z e d i n p o s t g a n g l i o n i c parasympathetic nerves to distinguish them from cholinergic nerves.…”
Section: Total Peripheral Resistancementioning
confidence: 77%
“…The role of NO in causing vasodilation during VVS has been elaborated earlier (74)(75)(76). In fact, Stewart et al (74) demonstrated that use of NO synthase inhibitors was helpful in attenuating the vasodilation during of VVS and is deemed promising as a tool for use in patients of recurrent VVS.…”
Section: Principles Of Management Of Vvsmentioning
confidence: 99%